DACHPt-Loaded Nanoparticles Self-assembled from Biodegradable Dendritic Copolymer Polyglutamic Acid-b-D-α-Tocopheryl Polyethylene Glycol 1000 Succinate for Multidrug Resistant Lung Cancer Therapy - Tsai, Hsiang-I; Jiang, Lijuan; Zeng, Xiaowei; Chen, Hongbo; Li, Zihuang; Cheng, Wei; Zhang, Jinxie; Pan, Jie; Wan, Dong; Gao, Li; Xie, Zhenhua; Huang, Laiqiang; et al. (Frontiers in Pharmacology, 2018)
The clinical applications of platinum-based antitumor agents are still largely limited by severe side effects as well as multidrug resistance (MDR). To solve these problems, we developed an 1,2-diaminocyclohexane-platinum(II) (DACHPt)-loaded nanoparticle (NP-TPGS-Pt) by self-assembly of poly(amidoamine)-polyglutamic acid-b-D-α-tocopheryl polyethylene glycol 1000 succinate (PAM-PGlu-b-TPGS) and DACHPt. NP-TPGS-Pt showed robust stability and pH-responsive DACHPt release profile in vitro similar to the PEG-containing nanoparticle (NP-PEG-Pt). Meanwhile, in contrast with NP-PEG-Pt, NP-TPGS-Pt exhibited efficient nanoparticle-based cellular uptake by the Pt-resistant A549/DDP human lung cancer cells and caused much more cytotoxicity than free Oxaliplatin and NP-PEG-Pt. Finally, this NP-TPGS-Pt was proved to perform outstanding inhibition of Pt-resistant tumor growth, much superior than free Oxaliplatin and NP-PEG-Pt. Thus, this NP-TPGS-Pt provides a novel powerful nanomedicine platform for combatting multidrug resistant cancer.